GUSTAVO, Zeh. Contrarresiliente. Rio de Janeiro: Editora Viés, 2019 (136 p.). - REA, Editor (Revista Espaço Acadêmico, 2021)
GUSTAVO, Zeh. Contrarresiliente. Rio de Janeiro: Editora Viés, 2019 (136 p.). Prefácio: Edson Passetti (PUC-SP)